Management of congenital ichthyoses: European guidelines of care, part two. (3rd December 2018) - Mazereeuw‐Hautier, J.; Hernández‐Martín, A.; O'Toole, E.A.; Bygum, A.; Amaro, C.; Aldwin, M.; Audouze, A.; Bodemer, C.; Bourrat, E.; Diociaiuti, A.; Dolenc‐Voljč, M.; Dreyfus, I.; et al.
Summary: These guidelines for the management of congenital ichthyoses have been developed by a multidisciplinary group of European experts following a systematic review of the current literature, an expert conference held in Toulouse in 2016, and a consensus on the discussions. These guidelines summarize evidence and expert‐based recommendations and intend to help clinicians with the management of these rare and often complex diseases. These guidelines comprise two sections. This is part two, covering the management of complications and the particularities of some forms of congenital ichthyosis. Abstract : What's already known about this topic? Various symptomatic treatment options exist for congenital ichthyoses, but there are no European guidelines. What does this study add? These European guidelines for the management of congenital ichthyosis may help to improve outcomes and quality of life for patients. Linked Comment: Akiyama. Br J Dermatol 2019; 180 :449–450. Plain language summary available online